Editorial for the special issue on micro/nano devices for blood analysis - Catarino, Susana Oliveira (2019)
The development of microdevices for blood analysis is an interdisciplinary subject that demands an integration of several research fields such as biotechnology, medicine, chemistry, informatics, optics, electronics, mechanics, and micro/nanotechnologies [...]